Diabetes Mellitus: A Public Health Challenge - Ydalsys Naranjo Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2016)
Diabetes mellitus is a syndrome characterized by hyperglycemia, due to an absolute or relative impairment of insulin secretion, insulin action, or both. It is a complex process of the carbohydrate, fat, and protein metabolism, which occurs as a result of such relative or complete impairment of insulin secretion from the β-cells of the pancreas or a defect in the insulin receptors.